Ammonia Toxicity: Integrating Environmental Health, Radiology, Nursing, and Respiratory Therapy - Alsarami, SALEH Abdulrahman; Albohomoud, Mohammed Saleh; Almojiwel, Turki Abdullah Mohammad; Alrashidi, Fatima Mealeth; Alanazi, Marzoq Joheem; Alanazi, Fahad Hawas; Al Woahaibi, Tamim Abdullah Abdulrahman; Alsouip, Sultan Khalid; Ageeli, Riyadh Essa; Alanazi, Abdulaziz Abdullah; Alqahtani , Abdullah Mohammed; ALESSAIMI, SANA MOHAIMEED (Journal of Ecohumanism, 2024)
Ammonia is a highly toxic, colorless gas with a pungent odor, widely used in industrial, agricultural, and household settings. It is naturally produced in the human body but becomes harmful when external exposure exceeds safe limits. Ammonia exposure occurs through inhalation, ingestion, or direct contact, leading to respiratory, gastrointestinal, dermal, and ocular injuries. Despite its widespread use, systemic toxicity from external exposure is rare, but localized damage can be severe and life-threatening.This article aims to provide a comprehensive overview of ammonia toxicity, focusing on its pathophysiology, epidemiology, clinical presentation, diagnostic evaluation, management, and prevention. It emphasizes the roles of environmental health, nursing, and radiology in mitigating risks and improving patient outcomes.The review synthesizes evidence from case studies, systematic reviews, and clinical guidelines to outline the mechanisms of ammonia toxicity, its clinical manifestations, and interdisciplinary management strategies. Key areas include toxicokinetics, histopathology, diagnostic techniques, and treatment protocols.Ammonia exposure primarily causes localized damage, with inhalation leading to respiratory distress, ingestion causing gastrointestinal burns, and dermal/ocular contact resulting in chemical burns. Severe exposure can lead to chronic lung disease, esophageal strictures, or vision loss. Diagnostic tools include imaging, endoscopy, and laboratory tests, while management focuses on decontamination, supportive care, and early specialist intervention. Preventive measures, such as proper ventilation and protective equipment, are critical in reducing exposure risks. Ammonia toxicity requires a multidisciplinary approach involving environmental health, nursing, radiology, and other specialties. Early recognition, prompt treatment, and preventive strategies are essential to minimize morbidity and improve outcomes. Public education and safety regulations play a vital role in reducing exposure incidents.